If dukun receive support from village funds, are they more likely to have motivation to find ways to prevent maternal and infant mortality? - Fitriana Puspitarani; Arinawati; Brian Sahar Afifah; Hasanbasri, Mubasyisir (BKM Public Health and Community Medicine, 2021)
Objective: This paper explores traditional healers role in developing an indigenous health approach in the context of making pregnancy safer in remote areas, where cultural resources are more accessible as compared to those of professionals. Content: In some remote areas, the half-hearted participation of traditional birth attendants in partnership maternal care programs signifies a lack of government trust in indigenous midwives. Even though the government assumes responsibility to increase access to trained health workers for women who choose traditional midwives to give birth, it is unlikely that the dukuns have the same response. Therefore, local actors need to bring this into their policy agenda. In the presence of the local government's engagement with the indigenous health approach, the bottom-up proposed usage of village funds for birth assistance, cultural ceremony, and referral transport costs help dukuns work confidently with village leaders to assure the child and mother's safety. Under local village leaders cultural support, the traditional birth attendants are more likely to accept the support as credit for their cultural practice and prepare for potential complications of pregnant women who need hospital referral. Not only that, local birth practitioners will use their autonomy to build their indigenous systems as a parallel approach to achieve the common goal both from the government and the local indigenous community. As the Pencerah Nusantara Program alumni working in remote areas in Central Kalimantan, we reexamine the nature of an indigenous health entity, growing from the cultural traditions in responding to reproductive health and maternal care.